Associations of prenatal exposure to five chlorophenols with adverse birth outcomes. (July 2016) - Guo, Jianqiu; Wu, Chunhua; Lv, Shenliang; Lu, Dasheng; Feng, Chao; Qi, Xiaojuan; Liang, Weijiu; Chang, Xiuli; Xu, Hao; Wang, Guoquan; Zhou, Zhijun
Abstract: Exposures to chlorophenols (CPs) have been linked with adverse health effects on wildlife and humans. This study aimed to evaluate prenatal exposure to five CP compounds using maternal urinary concentrations during pregnancy and the potential associations with birth outcomes of their infants at birth. A total of 1100 mother-newborn pairs were recruited during June 2009 to January 2010 in an agricultural region, China. Urinary concentrations of five CPs from dichlorophenol (DCP) to pentachlorophenol (PCP), namely, 2, 5-DCP, 2, 4-DCP, 2, 4, 5-trichlorophenol (2, 4, 5-TCP), 2, 4, 6-TCP and PCP, were measured using large-volume-injection gas chromatography-tandem mass spectrometry (LVI-GC-MS-MS), and associations between CP levels and weight, length as well as head circumference at birth were examined. Median urinary creatinine-adjusted concentrations of 2, 5-DCP, 2, 4-DCP, 2, 4, 5-TCP, 2, 4, 6-TCP and PCP were 3.34 μg/g, 1.03 μg/g, < LOD, 1.78 μg/g and 0.39 μg/g creatinine, respectively. We found lower birth weight 30 g [95% confidence interval (CI): −57, −3; p = 0.03] for per SD increase in log10 -transformed concentrations of 2, 4, 6-TCP and lower birth weight 37 g (95% CI: −64, −10; p = 0.04) for PCP, respectively. Similarly, head circumference decrease in associations with creatinine-corrected 2, 4, 6-TCP and PCP concentrations were also achieved. Considering sex difference, the associations of lower birth weight were only found among male neonates, while head circumference was associated with 2, 4-DCP and 2, 5-DCP only found among female neonates. This study showed significant negative associations between CPs exposure and reduction in neonatal anthropometric measures. The biological mechanisms concerning CPs exposure on fetal growth deserved further investigations. Highlights: Five chlorophenols (CPs) were measured in urine from 1100 the Chinese pregnant women. We examined the associations between maternal exposure to CPs and birth outcomes. Prenatal exposure to CPs were significantly negatively associated with birth sizes. Associations between exposure to CPs and birth outcomes were differed by neonatal gender. Abstract : This study suggested significant negative associations between maternal urinary CP concentrations and adverse birth outcomes.